Analisis Dampak Aktivitas Gerakan Literasi Sekolah (GLS) Terhadap Keterampilan Menulis Karangan Narasi Peserta Didik Kelas IV Sekolah Dasar - Ainayah Putri Maharani; St Y Slamet; Siti Istiyati (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2024)
This research aims to describe the impact of school literacy movement activities on the narrative essay writing ability of fourth grade elementary school students. This research is qualitative research using the results of students' narrative essay writing. The object of this research is the impact of literacy on students' narrative essay writing skills. Data collection uses observation, interview and documentation techniques. Data validity testing techniques use source triangulation and engineering triangulation techniques. The data analysis technique uses the Milles and Huberman data analysis model. The results of the research are that the literacy movement carried out can influence the learning outcomes of writing narrative essays for class IV students. This research shows that there are still some students who cannot explain the background indicators in a story. Setting indicators in a story include time, place and atmosphere. It is hoped that the implications of this research can be material for consideration and evaluation in literacy, especially in the activity of writing narrative essays.